2013
DOI: 10.1111/bjh.12541
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized trial comparing glucocorticoid monotherapy versus glucocorticoid and rituximab in patients with autoimmune haemolytic anaemia

Abstract: SummaryThe impact of first-line treatment with the anti-CD 20 chimeric monoclonal antibody rituximab in patients with warm-antibody reactive autoimmune haemolytic anaemia (WAIHA) is unknown. We report the first randomized study of 64 patients with newly diagnosed WAIHA who received prednisolone and rituximab combined (N = 32) or prednisolone monotherapy (N = 32). After 12 months, a satisfactory response was observed in 75% of the patients treated with rituximab and prednisolone but in a significantly smaller p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 26 publications
3
96
0
6
Order By: Relevance
“…The efficacy and safety of rituximab given in newly diagnosed primary wAIHA is being evaluated in a double-blind placebo controlled randomized trial (Clinical Trials.gov identifier: NCT01181154). The recent report of a doubleblind randomized prospective Danish study of 64 cases of wAIHA, mixing both primary and secondary wAIHA, provides strong evidence in favor of the early use of rituximab for wAIHA [11]. Results of another prospective but uncontrolled study were reported by an Italian group [10] and showed a high rate of efficacy of low-dose rituximab especially for wAIHA as compared with cold AIHA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The efficacy and safety of rituximab given in newly diagnosed primary wAIHA is being evaluated in a double-blind placebo controlled randomized trial (Clinical Trials.gov identifier: NCT01181154). The recent report of a doubleblind randomized prospective Danish study of 64 cases of wAIHA, mixing both primary and secondary wAIHA, provides strong evidence in favor of the early use of rituximab for wAIHA [11]. Results of another prospective but uncontrolled study were reported by an Italian group [10] and showed a high rate of efficacy of low-dose rituximab especially for wAIHA as compared with cold AIHA.…”
Section: Discussionmentioning
confidence: 98%
“…However, since 2000, rituximab has been increasingly used as second-or third-line treatment first in children and then in adults [8][9][10][11]. We previously reported the characteristics of 83 cases of AIHA, including 72 of wAIHA seen at our institution between 1980 and 2000, before the era of rituximab [5], and found an overall mortality rate of 18%.…”
Section: Introductionmentioning
confidence: 99%
“…In these atypical cases, the diagnosis, made after extensive laboratory workup and exclusion of other causes of hemolysis, is frequently deferred, with consequent delay in therapy. 1,2,[5][6][7] Treatment of AIHA is still not evidence based and is mainly accomplished according to expert opinions and individual experience, [8][9][10][11] with few prospective therapeutic trials [12][13][14][15] and large but dated comprehensive clinical studies. 16 Moreover, the temporal sequence of second-line options is still controversial, and no predictors of outcome are available.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 64 newly diagnosed wAIHA patients were treated eıther with steroid monotherapy or with combination of rituximab and steroid. The response rate and relapse free survival rates were statistically better in the combination group [46].…”
Section: Rituximabmentioning
confidence: 87%